Active Panoramic VR Video Play Using Low Latency Step Detection on Smartphone - Azeem Syed Muhammad; Ahn, Sang Chul; Jae-In Hwang (2017 IEEE INTERNATIONAL CONFERENCE ON CONSUMER ELECTRONICS (ICCE), 2017)
This paper introduces the use of walk-in-place (WIP) interface to actively control the speed of 360-degree panoramic virtual reality (VR) videos on a smartphone based head mounted display (HMD). For WIP interface, a low latency step detection algorithm is used. Then, through a user study, the effect of using this interface to control the speed of a 360-degree VR video is evaluated with respect to the amount of simulator sickness and presence in the environment felt by the users. The results of evaluation are compared with passive rotation only interface for watching 360-degree VR videos. It is found that our WIP interface is significantly better in terms of simulator sickness however for presence in the environment, not much difference is observed. The total score for simulator sickness is 41.41 for our WIP interface whereas the score for traditional rotation only method is 61.98. Individual factors that cause this difference are analyzed and discussed in detail. The paper concludes with limitations of our system and future work.
Keywords: virtual reality; cybersickness; panorama; walk in place